ANALISIS SWOT MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA DAN LOYALITAS GURU - Boruwati Sihombing, Febri; Recky, Recky; Abdul Aziz Mubarok, Dadan (Jurnal Daya Saing, 2026)
ABSTRACT Education is a fundamental sector in determining the quality of a nation's human resources, where teacher governance is a crucial instrument to realize learning goals to the maximum. This study aims to analyze how the application of SWOT analysis in Human Resource Management (HRDM) can be used as a strategy to improve teacher performance and loyalty in one of the private schools in the city of Bandung. Using a quantitative descriptive method, this study evaluates organizational strengths, weaknesses, opportunities, and threats through data collected from 10 teacher respondents through Likert scale questionnaires, observations, and interviews. The results of the internal factor evaluation (IFAS) showed a score of 3.55 which placed the school management in a strong classification, supported by teacher competence and high work commitment. Meanwhile, the external factor evaluation (EFAS) resulted in a score of 3.60, which indicates the organization's effectiveness in aligning strategies with opportunities such as government support and technological advancements. Based on the internal coordinate value of 0.85 and external coordinates of 1.20, the institution is in Quadrant I (S-O) which recommends the implementation of aggressive strategies or growth orientation. Through this strategy, the organization is expected to be able to utilize the professional capabilities of teachers to exploit external opportunities expansively to secure loyalty and improve the performance of educators in a sustainable manner. Keywords: Human Resource Management, SWOT Analysis, Teacher Performance, Teacher Loyalty.